Effects of neuromuscular responses during whole body vibration exercise with different knee angles - Gusi, Narcis (2012)
he purpose of this study was to compare the effects of whole body vibration (WBV) exercise using different knee angles on three-dimensional acceleration received in the lumbar region and neuromuscular activation of 8 muscles that were selected in order to determine their implications for rehabilitation. Thirty physically active women (mean ± SD; 21.7 ± 1.67 years) were randomized in three groups. The first group performed on the platform with 15, 45 and 90º knee flexions, the second group with 45, 90, 15º, and the third group with 90, 15, 45º. The WBV frequency was 12.6 Hz. The acceleration was recorded by a tri-axial accelerometer (Biopac) attached on the skin at L3 level and the electromyography (EMG) was recorded by surface active electrodes (Biopac) on the extensors and flexors of the knee and lower trunk. The lateral acceleration was 3 times greater (p< 0.05) at the vertical line in 3 angles of flexion, and the vertical line was 2 times greater (p< 0.05). Maximum accelerations: lateral (11-13 g) and vertical line (6-7 g) had increased when reducing the knee-flexion angles. In conclusion, WBV using the Galileo platform transmits more lateral neuromuscular and mechanical stimuli than vertical stimuli. A smaller degree of knee flexion transmits a greater mechanical stimulus, and a higher flexion of the knees implies an increase of muscular activity in the vastus internus muscle. These findings open the possibility of different applications.